THE "BEGEPEN" TRADITION AS A SYMBOL OF PEACE AND UNIVERSITY IN THE EFFORT OF STRENGTHENING THE NATION'S SELF IN THE TRADITIONAL SERVICES OF THE ODUNG BAORAJA TRIBE (Lectio: Journal of Language and Language Teaching, 2025)
INTRODUCTIONThe tsunami that hit Waiteba, Lembata, East Nusa Tenggara Province in 1979, caused members of the Odung tribe and several other tribes in Baoraja, Atadei sub-district, to eventually spread to several areas both inside and outside Lembata. Most of the Odung tribal families were evacuated to Loang, the capital of Nagawutung sub-district. Since the majority of Odung family members live in Loang, it was decided to move the traditional house of the 'Odung' tribe to Loang. All traditions and processions carried out at each traditional ceremony remain original and in line with what has been passed down from generation to generation.In order to gather and unite the Odung tribesmen scattered throughout Indonesia, it was decided to hold a tribal reunion event every five years. With several traditional ceremonial events, namely the entrance ceremony to the 'gew una Rayan' tribal house and the 'begepen' peace meal ceremony. The traditional house or una rayan is the main house of the tribal people. The house is a place to gather with tribal people at every traditional ceremony. The ceremony of entering the traditional tribal house is intended to reunite with relatives as one family and to ask for the blessing and blessing of the ancestors for all works in their respective places of duty while still serving the tribe as a unifying symbol and source of strength. While begepen teaches about the values ??of togetherness, brotherhood and strength. These values ??provide advice and direction for human safety in living their lives. These two ceremonies are carried out not only as an effort to unite tribal members but also as a strategy to introduce early all the processes of every traditional ceremonial for the next generation of the Odung tribe.The peace meal ceremony is a tradition that is still maintained and carried out in almost every area of ??the Lembata district. In the kedang the peace meal is known as 'mawu wowo tutuq toyeq'. In Lebatukan District, it is known as 'bet'ti gole'. In Ile Ape it is known as 'tapan holo huli boke'. While at Atadei it is better known as 'begepen'. The begepen ritual is an integral part of every traditional ceremony.Moeliono (1991:6) states that customs are rules and regulations that are commonly obeyed or carried out since time immemorial. Customs have an important role in the systems and values ??adopted and run by the community. Every traditional ceremony essentially aims to create a society that is safe, peaceful, and obedient to customary provisions.Tribal people believe in togetherness and a sense of brotherhood as tribal children, then they create strength. All the turmoil or problems that hit the tribesmen will be easily resolved. With the begepen ceremony all the tribesmen felt strengthened. Begepen As A Symbol Of Peace And University Of Tribes And AncientsThe 'begepen' ceremony is part of the original Lembata culture and ancestral heritage which is guided directly by the 'ata beruin' (tribal chief) who really understands customs and all matters related to customs. On the day of its implementation, all tribesmen need to prepare the materials needed for the begepen ceremony including:Kehaler in the form of a medium tray woven from palm leavesNowing is a kind of sarong traditionally woven for men. Nowing is folded and placed in the halerKenik is rice. Prepared handfuls as food ingredients for peace rice. Rice is wrapped in 'kelomak' corn husks and placed on a sarongCandlenut: One whole grain plus four whole grains of rice. The two are put together, wrapped and tucked between the folds of the nowing/holsterBraha dua mongan: eight rolls of white cotton, then rolled again and put together into two mongan with four rolls eachBraha Tegan: six cotton rolls and separated into three parts with two rolls each. Ceremony in Front of the Entrance of the Tribal Traditional HouseThe begepen ceremony begins with a ceremonial ceremony in front of the entrance of the tribal traditional house which is guided directly by the tribal chief. This ceremony is carried out solemnly by all tribesmen. The event started by placing two mongan bras on the right and left sides of the kehaler. Then also put the tension bra. Two tension brahas are placed on the ground which will then be placed on top of the halter. The other two middle brahas are placed to the north of the kehaler (the entrance to the big house), and the other two are placed to the south of the kehaler (the direction of the exit). Haler with begep ingredients, placed on top of the tension bra which is located in the middle. After the procession in front of the traditional house was completed, the tribal leader 'ata beruin' began to say a prayer asking for the ancestral blessing 'amet prat' as follows: Kem tedek gepar mio ina ama tua maguNebe kem heri, kem begepenIpo lolunge, hem kem waolem ganeKem uyo keniker, na lau khal tua meaKem tibanga wain, di lau kono ehakKem menunge tuak, noko mere kono ehakGero jema be, ba nuhem deu gelikehe, elewem deu gewalet keGero jema be, ba no tuak neu burange keGero jema be, ba no keleruk neu belobeke enKeniri belolonge helaiti kem pekeng-tiwang dipoTek gahip hi, tek bage hiTek guat hi, tek hurat hiKeniring nor laite, kempil dokeMaketi dor oleng kem bak moling The loose translation:We convey to you the ancestorsWe serve this peace food for youWe will cook and eat togetherWe eat and drink together in one containerAnd also drink in the same containerWe drink palm wine on the same treeMaybe in the past there was a wrong and painful word          Maybe we were wrong in the past because we were drunk with palm wine and betel nutMisunderstanding all this time, this time we also leaveCan't be counted, can't be dividedWe will not remember and repeat againWe regret all the mistakes we have madeAnd now we are starting to renew ourselvesAfter finishing the prayer, kehaler and its contents are stored in the traditional houses. 'Kenik begepen' or peace rice is taken and mixed with other raw rice and then cooked together. A red rooster is slaughtered and then cooked in a sauce without spices.Peace Meal Ceremony 'kane begepen' (explained what ingredients are served above the booth for megepen)There are two important parts to this peace meal.Pau paraw ina ama tua magu (feed the ancestors'). This is a form of respect for the ancestors. This ceremony begins by giving offerings in the form of small parts of the sacrificial animal, in this case a chicken. Take a little meat from the heart, liver, toe tips, wing tips, the tip of the chicken's beak plus a little rice and gravy. All offerings are placed above the booth and divided into four parts. Then the palm wine is poured four times, once for each portion of the dish. While pouring palm wine, the tribal chief recited the 'amet prat' prayer to the ancestors as follows: Kem tedek gepar mio ina ama tua maguKem begem mio ga mol men molNe pon kem ga puje men dorTea rebe kem gane kem kenik begepen The loose translation:We convey to you the ancestorsWe serve you food and drinks first to eatWe eat and drink after you eatToday is the day of unity by eating   together for peace     Eat the peace of the 'begepen' family.After finishing the prayer, the tribal chief began to eat first (ui ga nol) and then asked to eat (nepon oyan wihe ui dor) with all the tribesmen. Those who are unable to attend can be represented by mentioning their names and then eating on their behalf as a sign that they are also present at this banquet. All the available food and drinks were spent together with joy in a feeling of togetherness.  “The Candlenut Breaking Ceremony”  Asking for the Ancestral Blessing ‘Beto Mirek – Dulat Kenitoh’This ceremony was held the next day after the begepen ceremony. The Kenitoh dulat process is the process of obtaining ancestral blessings through the hands of the tribal chief, by placing a symbol in the form of a cross on one's forehead. The candlenut and four grains of rice at the 'begepen' ceremony yesterday were taken, the candlenut was broken by the tribal chief with a traditional crusher. The contents of the candlenut are chewed together with four grains of rice and three koter leaves. After being chewed, all the ingredients were removed and accommodated on a larger sheet of koter leaf. The chieftain was the first to dip the thumb of his right hand into the material and mark his own forehead with a cross. All the tribesmen lined up and one by one came forward to be slapped. The tribal members who were not present were pronounced their names in front of the tribal chief as a sign that the person concerned was also present at the 'dulat kenitoh' event. The meaning and symbols of the objects used in the begepen ceremony:The influence of globalization is certainly very influential on the sustainability of the customs of a region. The sustainability of our culture is highly dependent on the community itself. This is the biggest challenge to maintain the existence of our local cultures. Its existence will be further eroded when we do not introduce the local cultures that we have to the next generation. Clifford Geertz with his Interpretative approach sharpens the notion of culture as a system of conceptions inherited from previous generations and expressed in symbolic form with the help of humans to communicate, preserve and develop knowledge and attitudes towards life.Therefore, it is important for us to introduce and teach them about the symbols of our culture and customs continuously by involving children in every traditional ceremony. Here are the meanings and symbols of the objects used in the begepen ceremony:Kehaler: in the form of a medium tray made of woven palm leaves as a symbol of all tribesmen being united and gathered in one placeA nowing or original woven sarong that is woven by oneself as a unifying symbol in one family bondCandlenut as a wound healer and medicine. Symbol of forgiving and forgiving each otherThe four grains of rice as a symbol of peace. The symbol of all who come from the four winds, united both in eating together and the sign of the dulat kenitoh Green broadleaf koter, is a kind of forest tree with wide leaves that can accommodate dew and is also used as medicine. Symbolized as a reservoir of coolness. All citizens are united in freshness and coolness by keeping away anger, envy and swearing.Braha is cotton as purity and sincerity.  Pau paraw means the process of giving food, offerings or offerings to ancestors.Konok is a drinking container as a substitute for a glass made of coconut shell.Tuak is a traditional drink made from palm trees, coconut and palm sugar. The effect of modernization that is going so fast has greatly influenced the existence of our own local culture. Our current generation is more likely to choose and love foreign cultures than their own. Their identity as a generation with regional culture seems to be disappearing. This is a serious national problem that needs to be addressed quickly, accurately and wisely. The reality that occurs in every traditional ceremony, children are more likely to enjoy eating and drinking without having to learn to fully understand how the traditional ceremonial process fully takes place. In fact, there are many noble values ??obtained and used as a foothold in social life.According to Manuaba (1999: 9) when these realities and problems are not immediately anticipated, it is certain that our future generations will lose their own cultural roots and foundations. They certainly will not have a clear national identity and will lose their regional sense, soul and spirit and the spirit of Indonesia because they are not embedded in these values.Manuaba's concern is clearly evident by looking at the reality that is happening today.When this regeneration process does not work, the door to extinction is ready to open, swallowing all the culture and wealth of our region without being left behind and we only become individuals who walk without our own cultural footing and foundation. Therefore, children need to be involved in their community, where they realize their existence as autonomous and social beings. In their social community they will learn about values, social systems, symbols, social norms and concepts that are useful and meaningful for themselves and their social groups. Through these things, humans communicate, preserve and develop their knowledge about life and their attitudes towards life. Bascon (Danandjaya, 1997:19) states that there are 4 roles of regional culture, namely:As a projection system (projective system) reflecting shared/collective idealsAs ratification of cultural institutions and institutions.As a child education tool (Pedagogical device)As a means of control so that the norms of society will always be obeyed by its collective membersIn an indigenous community, a strong bond between culture and human life will form a sense of solidarity among members. Customary rules have an important role in regulating all activities, discourses, dialogues, and social discourses as a projection system to realize a common goal. In addition, custom has an essential factor for community identity and integration. Custom   is a collective self-interpretation system that becomes a symbol in which people become aware of themselves and think about collective existence.In other words, custom is nothing but a projection of society itself in human consciousness. Thus the cultural symbols will remain sustainable in the continuity of social life.The close relationship between society and culture has formed a close bond between customs, beliefs, society and culture. Begepen can be a tool to ratify a cultural institution and institution.Children are the next generation of the nation. In their hands the fate of our culture is at stake. Modernization has created a new culture, an instant-paced culture. This has a direct impact on the existence of our own culture.Therefore, culture and local wisdom values ??must be intensively introduced and taught to our children as an effort to maintain our identity as a cultured nation. This is because begepen has elements that cannot be separated from knowledge and education.Regional culture has customary rules that must be obeyed and carried out in an indigenous society. Begepen has rules that indirectly reflect to the community the norms that must be adhered to in order to create a harmonious life between tribesmen and society. CONCLUSIONSBasically, behind the begepen ceremony in the traditional house of the Odung tribe, there is a deep meaning that is implicit and very important to learn, live and carry out. The implementation of the Begepen ceremony is a reflection of the independence of the tribal community to interpret the values ??of brotherhood, togetherness, and peace which are the local wisdom of the Lembata community in organizing and building social glue for harmonious living together. Thus the values ??of socio-cultural traditions can be systematically inherited from generation to generation (social heritage) as a form of preserving local cultures so that future generations can continue to recognize and carry out their own regional culture. We must maintain and preserve local wisdom which is a mirror of our identity by seeking truth values ??through science and research by encouraging people to develop a culture that respects human dignity as civilized human beings. Therefore, as parents, community leaders, religious leaders, traditional leaders, government leaders and other community task holders, we must feel called to continue to explore the points of local wisdom by continuing to introduce and teach every noble value (kindness) to our children and young generation so that they can find themselves as autonomous and social beings in building relationships with themselves, others, the universe, and their God.   References  Moeliono, M. Anton. (Ed.) 1991. Kamus Besar Bahasa Indonesia. Jakarta: Balai  Pustaka Danandjaja, James. 1997. Folkor Indonesia : ilmu gosif, dongeng dan lain-lain.         Jakarta: Pustaka Utama Grafiti.  Taum,Yosep. 2016. Wawasan Kebangsaan dari Perpektif Budaya Flores. http://repositori.perpustakaan.kemendikbud.go.id. Manuaba, Putera. 1999. Budaya Daerah dan Jati Diri Bangsa : Pemberdayaan Ceritera  Rakyat  Dalam Memasuki Otonomi dan Globalisasi. Surabaya : Journal Universitas Airlangga. Journal.unair.ac.id/download-fullpaper-06-Manuaba.pdf. Diakses pada 3 Agustus 2017 Alam, Bachtiar.1997. Antropolologi dan Pembangunan. Jakarta: Makalah Antropologi Indonesia 54. http://carialamatnaya.go.id Odung, Kwihal Yan.2002.Catatan Pribadi: Acara Begepen Rajan Warga Suku